Sistem Kerja, Prosedur Kerja dan Pengembangan Karir Terhadap Produktivitas Kerja Pegawai PTPN III - Juan Felix Hutabarat; Fenny Krisna Marpaung; Ayub Millennium Simare Mare; Fauzi Fauzi (Journal of Management and Bussines (JOMB), 2023)
This research aims to test and analyze the influence of work systems, work procedures, career development and work productivity of PTPN III employees. The research method used is quantitative research with the research population being all PTPN III employees totaling 683 people with the sample used being 253 people using simple random sampling. The data analysis method uses multiple linear regression. The research results show that the variables of work systems, work procedures and career development partially or simultaneously have a positive and significant effect on the work productivity of PTPN III employees. In conclusion, work systems, work procedures and career development can increase employee work productivity. Keywords: Career Development, Work Productivity, Work Procedures, Work Systems